Strategi Guru Pendidikan Agama Islam Dalam Meningkatkan Motivasi Belajar Siswa - Palupi Kinansih; Sri Haryanto; Muhtar Sofwan Hidayat (JURNAL ILMIAH NUSANTARA, 2025)
This study explores strategies used by Islamic Religious Education (PAI) teachers to increase learning motivation among second- and fifth-grade students at SD Negeri 3 Pagedongan, Banjarnegara. Motivation is vital in influencing students’ enthusiasm, discipline, and academic outcomes, yet many still lack interest in PAI subjects. Using a qualitative descriptive approach, data were gathered through observation, interviews, and documentation, focusing on the PAI teacher. The study found that motivation was enhanced through strategies such as creating positive student-teacher relationships, using engaging media (songs, videos, discussions, drama), and providing spiritual reminders about learning as worship. Methods were adjusted to student levels: playful techniques for grade II and more complex tasks for grade V. Factors supporting success included teacher enthusiasm, student curiosity, parental support, and creative media. Challenges included low student awareness, peer influence, and less conducive classroom conditions.